Pengaruh Tekanan Terhadap Deflection dan Shear Stress Helical Compression Spring Pada Press Pallet - Irwansyah Irwansyah (CV. IRA PUBLISHING, 2022)
The author describes the object of observation in this final work as the helix compression spring. The helix compression spring is used to reduce pressure, and it works based on the amount of compressive force exerted by the press plate on the pallet. The pallets used are nine types of pallets with three main paper sizes, namely A4, F4, and B5. This observation aims to study the extent of the relationship between the variables of pressure, deflection, and spring shear stress. Based on the results of the discussion obtained, the pallet that receives the most significant compressive force, deflection, and shear stress is the F4 5 plate pallet, and the pallet that gets the minor compressive strength, deflection and shear stress is the B5 3 plate pallet. This proves that the pressure is directly proportional to the deflection and shear stress of the spring.